Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Dikelas Iv SD GMIM V Tomohon - Jeanne M. Mangangantung; Merlin I. Penteno; Brianne E. J. Komedien (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to improve the learning outcomes of fourth grade students at SD GMIM V Tomohon by applying the discovery learning model. The research subjects were fourth grade students with a total of 13 students. This study used the classroom action research (PTK) method, according to Kemmis and Mc. Taggart (in Aqib Zainal, 2006:31) which consists of four stages, namely planning, implementation of action, observation, and reflection which is applied in the second cycle. Data collection techniques used in this study were observation and test techniques. Data collection by observation techniques using observation instruments, while the test by giving a number of questions or evaluations. The data analysis technique uses the formula KB = x 100%. The results in cycle I obtained student learning outcomes of 71.53% of the total 13 students, only 5 students managed to receive the material well and 8 students who did not succeed. Thus, after correcting the deficiencies in the first cycle, the second cycle research obtained learning outcomes with a percentage of 90.76% or it can be said to be successful. Thus it can be concluded that the application of the discovery learning learning model can improve science learning outcomes about Wind Energy Sources in class IV SD GMIM V Tomohon. By increasing student learning outcomes, it is suggested that class teachers are expected to be able to apply the discovery learning learning model, in science learning activities in elementary schools.